Sapodilla (Manilkara zapota) Broth as an Alternative Media for Candida albicans - Chen Chui Ying; Ine Kuswardinah; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To determine whether sapodilla can be used to grow Candida albicans. Among all the high galactose and arabinose content fruits, the sapodilla was chosen because it is available year round and can get easily in market. Other than that, it also contains vitamins, calcium and phosphorus which are very useful for fungi growth.Methods: This study used an experimental study as a method of research. The researcher culture Candida albicans on the experimental sapodilla media and identifies the morphology of the fungi by using Gram staining method. The experiment will be replicated two times to get accurate result. The procedure of this experiment constitute of sapodilla media preparation, sapodilla media observation, organism preparation, planting and incubation, observation of fungal colonies and identification of the fungi.Results: In 0%, there was no fungal growth at all. In 5%, there was mild density of fungal colonies. In 10%, there was moderate density of fungal colonies and in 15% the fungal grew with very dense colonies.Conclusions: Sapodilla (Manilkara zapota) broth can be used as an alternative media for Candida albicans.Keywords: Alternative media, Candida albicans, Sapodilla brothDOI: 10.15850/ijihs.v5n1.965